Impact of a Supernova Remnant on the Physical and Chemical Properties of an Infrared Dark Cloud - Petrova, Ana-Mari (My University, 2023)
Massive stars play a fundamental role in the evolution of the Universe, but the process that initiates their formation from molecular clouds remains much debated. One way to understand the initial conditions required for massive star formation is to study Infrared Dark Clouds (IRDCs), which are cold, dense regions in the interstellar medium (ISM) seen as dark features at infrared wavelengths. Stellar feedback in the form of supernova remnants (SNRs) and HII regions has been proposed to have a large impact on the physical and chemical state of IRDCs. However, whether this feedback enhances or suppresses star formation, i.e., whether it is positive or negative feedback, is uncertain. Here we study the physical and chemical conditions of the IRDC G34.77-0.55, which is in close proximity to the SNR W44 and the HII region G34.8-0.7. We observed 13CO(1-0) and C 18O(1-0) line emission from the IRDC and its surroundings using the Green Bank Telescope (GBT). We also observed several other molecular line species tracing higher density conditions using the Instituto de Radioastronomia Milimetrica (IRAM) 30m telescope. Mass surface density and temperature maps derived from archival Spitzer and Herschel Space Telescope data were also utilized. With these data, we first study the kinematics, by producing first moment maps that reveal a velocity gradient from high (more redshifted) to low (more blueshifted) values from the HII region side to the SNR side. This may indicate that the IRDC is located beyond the HII region and in front of the SNR. In addition, we also study the abundances of various species, especially CO, HCO+, and N2H+. In cold, dense regions CO freezes out from the gas phase to form CO ice coatings on dust grains. We present maps of the CO depletion factor, which measures the extent of this process, and study how it depends on physical conditions. Combined with the abundances of HCO+ and N2H+, astrochemical modeling is applied to constrain the age of the cloud to be ∼ 105 - 106 yr and the cosmic ray ionization rate (CRIR) ∼ 10−17 s −1 . This CRIR is several times larger than that inferred by identical methods in another IRDC, which may indicate the impact of the W44 SNR on G34.77-0.55. However, the overall rate is still significantly lower than that of the diffuse ISM, suggesting a role for absorption or screening processes that reduce the efficiency of CR propagation into IRDCs. We discuss the location and dynamical state of dense gas structures in the IRDC and their relation to the surrounding feedback.
Keywords: IRDC G34.77-00.55 - astrochemistry - SNR W44 - star formation.